Photography and diaspora: Interpretations and explorations in Indian migration studies - Lewis, Sarojini (Journal of Indentureship and Its Legacies, 2023)
This essay utilizes the rich photographic collections of the Herrnhut Archive, Rijksmuseum and Tropenmuseum to explore alternative ways of understanding the colonial Indian labour diaspora, to infuse new meanings into old pictures and to draw upon the reinterpretation of historical images to reframe personal female migration stories from an artistic perspective. This essay presents an overview of the photography of colonial subjects in India and of her diaspora, and discusses the symbolism and representations of selected case studies of individuals and groups in the Dutch colonial territory of Surinam. From this analysis, the author presents the significance of her findings for the evolution of her own work as an Indian woman of diaspora heritage exploring new ways of articulating complex personal and group identities through the medium of exhibitions and installations.